Bulk plasmon polariton based structured illumination microscopy by utilizing hyperbolic metamaterials. (4th May 2021) - Liu, Xiangzhi; Kong, Weijie; Wang, Changtao; Pu, Mingbo; Li, Zhenyan; Li, Xiong; Ma, Xiaoliang; Luo, Xiangang
Abstract: Because structured illumination microscopy (SIM) has the advantages of wide-field, rapid imaging, and biocompatibility, it is widely used for super-resolution imaging of living cells. Here, we demonstrate a new super-resolution imaging method—bulk plasmon polariton based SIM (BPPSIM), which combines the SIM with the hyperbolic metamaterials (HMMs). By utilizing an HMM composed of a multilayer metal/dielectric film, a deep subwavelength bulk plasmon polariton is obtained. The imaging resolution of BPPSIM can be improved by the uniform and wide-field structured illumination pattern with high spatial frequency, benefiting from the filtering effect of HMM for the spatial frequency spectrum. The resolution of the recovered images by BPPSIM has been increased to 1/8 of the fluorescence wavelength, which is 2.7-fold enhancement in resolution compared with traditional fluorescence microscopy. This proposed approach demonstrates the operability and flexibility of the structured illumination pattern and can be used in a simple, wide-field and super-resolution fluorescence microscope.